PENGARUH PENGALAMAN DAN KEMAMPUAN PEMERIKSA INVESTIGATIF TERHADAP EFEKTIVITAS PELAKSANAAN PROSEDUR AUDIT INVESTIGASI DENGAN SKEPTISME SEBAGAI VARIABEL MODERASI - Sahreza Harahap; Friska Debora Maria (Prosiding Seminar Nasional Pakar, 2020)
In this study, the effectiveness of the implementation of audit procedures in the disclosure of fraud means that audit procedures must be passed and carried out properly, starting with the initial information review stage, audit planning, conducting audits in accordance with standards, using audit techniques, as well as reporting and following up to with proof in court, all of which are guided by established audit standards. The main objective of this study is to examine and analyze the Effects of Investigative Investigators' Experiences and Capabilities on the Effectiveness of Audit Procedures in Revealing Fraud. This study has a formula: Does the experience and ability of investigative investigators have a positive effect on the effectiveness of the implementation of audit procedures in exposing fraud.